2002
DOI: 10.1021/jp025554y
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Characterization of the P−C Bonds in Ylides of Phosphorus

Abstract: The aim of this paper is qualitative understanding of the behavior of electrons in the ylides of phosphorus by means of the sharing amplitudes and the volume-point sharing indices (Fulton, R. L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Very recently, in a study by Sánchez-González, Martínez-García, Melchor, and Dobado (SMMD) on similar species, the authors found that some increases in the bond multiplicity are not reflected in the DIs, and, consequently, SMMD cautioned against the use of DIs as a measure of bond multiplicity or bond order (vide supra). Mitrasinovic in a series of works , has studied the bonding in some simple ylides using the Fulton bond orders (eq 38) computed at the MP2 level of theory. Mitrasinovic showed that the DIs indicate that the P−C and N−C bonds in PH 3 CH 2 and NH 3 CH 2 are single bonds, whereas in PHCH 2 and SH 2 CH 2 the DIs are between the values corresponding to prototypical single and double bonds.…”
Section: 22 Examples and Applications In Chemistrymentioning
confidence: 99%
“…Very recently, in a study by Sánchez-González, Martínez-García, Melchor, and Dobado (SMMD) on similar species, the authors found that some increases in the bond multiplicity are not reflected in the DIs, and, consequently, SMMD cautioned against the use of DIs as a measure of bond multiplicity or bond order (vide supra). Mitrasinovic in a series of works , has studied the bonding in some simple ylides using the Fulton bond orders (eq 38) computed at the MP2 level of theory. Mitrasinovic showed that the DIs indicate that the P−C and N−C bonds in PH 3 CH 2 and NH 3 CH 2 are single bonds, whereas in PHCH 2 and SH 2 CH 2 the DIs are between the values corresponding to prototypical single and double bonds.…”
Section: 22 Examples and Applications In Chemistrymentioning
confidence: 99%
“…As can be seen in Tables 2 and 3, the calculated geometries of H m DAH n complexes agree quite well with previously reported theoretical data. [6][7][8][9][10][21][22][23][24][25][26][27][28][29][30][31][32][33] For the H m DAH 2 complexes (A = C, N + , Si, P + ), there is a reasonable correlation between the t-angle, which measures the degree of planarity at the A atom, and the SDE ST values (DE ST is the energy difference between the singlet and triplet electronic states for DH m and AH n . Alternatively, H 3 DAH 2 bonding can also be described as the interaction of H 3 D with an n 2 singlet AH 2 (as shown in structure 3), or with a p p 2 singlet excited AH 2 (as shown in structure 4); 34 specifically, an ylidic bond can be viewed as a dative bond.…”
Section: Methodsmentioning
confidence: 99%
“…The MP2/aug-cc-pVTZ method should be the best choice for estimating the bond strength of the ylide compounds because the MP2/aug-cc-pVTZ BDEs are comparable to CBS-QB3 data. 7,13 The electronic structures of the singlet H m DAH n complexes can be formed from either two triplet or two singlet fragments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the phosphorus-and sulfide-ylide species possess both ionic and double-bonding characters. [12][13][14] They have separately positive (P-or S-atom) and negative (C-atom) charges. This motivates us to speculate whether any radicals derived from the P-or S-ylides can have unique chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%